Characterization of the DNA-binding site in the ferric uptake regulator protein from Escherichia coli by UV crosslinking and mass spectrometry - Tiss, Ali; Barre, Olivier; Michaud-Soret, Isabelle; Forest, Eric (FEBS letters, 2005)
Ferric uptake regulator protein (Fur) is activated by its cofactor iron to a state that binds to a specific DNA sequence called ‘Fur box’. Using mass spectrometry-based methods, we showed that Tyr 55 of Escherichia coli Fur, as well as the two thymines in positions 18 and 19 of the consensus Fur Box, are involved with binding. A conformational model of the Fur–DNA complex is proposed, in which DNA is in contact with each H4 [A52–A64] Fur helix. We propose that this interaction is a common feature for the Fur-like proteins, such as Zur and PerR, and their respective DNA boxes.